A Practical Method for Identifying Lesions Caused by HIFU Application: Egg White Phantom [HIFU uygulamasi sonucu oluşan lezyonlarin belirlenmesi için pratik bir yöntem: yumurta aki fantomu] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
The widespread use of HIFU treatment method in the clinic depends on the effective and safe dosimetric studies. In this study, an easy-to-produce, cost-effective, transparent and egg-white polyacrylamide-based phantom is produced which can be observed in real time synchronized form with HIFU application. HIFU was applied on phantom at different voltage values and different times and the crosssectional areas and volumes of the lesion regions were calculated in MATLAB program by using image processing methods. © 2019 IEEE.
Keywords: Acoustic parameters; Cancer; HIFU; Image processing; Phantom; Temperature increase